Pemanfaatan Aplikasi Computer Based Test (CBT) Pada SMA swasta HKBP Hutabayuraja untuk meningkatkan efektivitas proses evaluasi Belajar Siswa - Jaya Tata Hardinata; Reagan Surbakti Saragih; Dudes Manalu; Christa Voni Roulina Sinaga; Ferri Ojak Immanuel Pardede (LPPM STIKOM Tunas Bangsa, 2022)
Utilizing Computer Based Test (CBT) application at HKBP Hutabayuraja private high school can enhance the effectiveness of the student learning evaluation process by improving accuracy and objectivity, saving time and costs, and motivating students. However, the lack of knowledge among teachers and staff about CBT remains a major obstacle in implementing this technology. Hence, socializing and training teachers and staff is crucial to maximize the benefits of this technology, while also ensuring the protection of student data from unauthorized use. The CBT application provides flexibility in terms of time and place, as it can be accessed through a computer or mobile device, allowing students to carry out learning evaluations anytime and anywhere. To optimize its usage, adequate training and socialization for teachers and staff is necessary. The use of CBT applications offers numerous benefits for both teachers and students in the learning evaluation process, highlighting the need for broader implementation of technology such as CBT applications to increase efficiency and effectiveness in evaluating student learning.